Relação fraterna na fase adulta: significados atribuídos ao longo do tempo - um estudo de caso - Salles, Ana Claudia Oliveira (2014)
The aim of this research is to understand the meaning given to sibling relationships over time and how these relationships are inserted in the family history. The study was based on the Family Systemic Approach and the current references about sibling relationship during the childhood, adolescence and adulthood. A case study was performed in one family of four adult brothers, two women and two men, between the ages of 29 and 40. A compound procedure was used by applying two scales Life Spam Relationship Sibling (translated to be used in this study) and Parental Boding Instrument (PBI version in Portuguese), an initial questionnaire with open questions, besides a group interview with all brothers and sisters together and an individual interview with the mother. It was verified in this study that the fraternal bounds were built, from the childhood to the adulthood, based on the unit and mutual support, offering a feeling of closeness even without the frequent coexistence. The sibling relationship in this family functions as net of support, solidarity and friendship. The clearness of the boundaries established between the original family and the nuclear family was an essential aspect to the conjugality and functional parenthood. Another important factor was the parents mediation in their children s relationship during their childhood. This mediation provided a development of children s resources to solve conflicts, facilitating the construction of good communication between the siblings and the respect for differences among them